A Study of the Fuzzy approach to Multiple Attribute Decision Making used in Investment Company: - (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The typical approach to grey-area analysis is used in this method. The fuzzy eigenvector of thefuzzy attribute evaluation space is used in the proposed enhanced fuzzy AHP technique, whichsignificantly outperforms previous similar algorithms. It has a great resolution and is completely impartial.This technique takes into account the fact that any individual or group making a decision may havelimited information about the input parameters of a choice that must satisfy several criteria. This article'sstrategy is easy to understand and use, and it demands less dogmatic thought from decision-makersthan competing strategies. Weight inputs may be a fuzzy number between two intervals. Fuzzy valuesrepresenting generic intervals may be used to submit alternative performance evaluations. After theevaluations for both convenience and effectiveness have been normalized, a composite utility value maybe calculated within a certain range.